ŚWIĘTA, ŚWIĘTY – CHARAKTERYSTYKA PORÓWNAWCZA OBRAZÓW SKOJARZENIOWYCH - Niećko-Bukowska, Bożena (Acta Neophilologica, 2018)
This article focuses on comparative characteristics of associative images of female and male saints. The study was aimed to reconstruct and compare associative representations. The respondents were 80 students of Adam Mickiewicz University in Poznań. The methods used in the study included a “but-test” (X is A, but…) and a free association test. The data collected (received from respondents) for a saint-woman demonstrate that she is frequently attributed with features such as e.g., humble, merciful, virtuous/chaste, while a saint-man is typically presented as: strong, principal, adamant. The image of a female and male saint may strongly depend on the general image of a woman and man (respectively). According to the participants of the present study, both female and male saints have common attributes. Features of a saint include: goodness, altruism, helpfulness, devotion to God and faith, making miracles, courage, high-mindedness, serenity and humility.